Family Decision Making in Utilization of Pregnancy and Maternity Services - Barus, Emi Br (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Efforts to improve maternal and child health in Indonesia have been carried out for a long time, namely with quality maternal health services starting from the time of pregnancy, delivery assistance by trained health personnel, postpartum care for mothers and babies, special care and referrals if complications occur, obtaining leave pregnancy and childbirth, and access to family planning. Maternal health service is a place used to carry out service efforts. Health services for pregnant women are realized through the provision of antenatal care at least six times during pregnancy. Objective: This study was to determine the factors of family decision making in the utilization of pregnancy and delivery services. Methods This research will use an analytic type using a cross-sectional design. The number of samples in this study were 40 people with a duration of 7 months. Total sampling technique. Data analysis consisted of univariate analysis and bivariate analysis with the chi-square test. Results: The results of the study showed that the majority of the factors of good knowledge were 20 people, the majority of the high economic factors were 21 people and the mileage factor was 21 people. Conclusion: There is a relationship between knowledge, economics and distance traveled with the utilization of pregnancy and delivery services with a p value of 0.000. This research is expected to be an input for pregnancy and delivery services so that they can be maximized. Abstrak: Upaya untuk meningkatkan kesehatan ibu dan anak di Indonesia telah lama dilakukan, yaitu dengan pelayanan kesehatan ibu yang berkualitas mulai dari saat hamil, pertolongan persalinan oleh tenaga kesehatan terlatih, perawatan pasca persalinan bagi ibu dan bayi, perawatan khusus dan rujukan jika terjadi komplikasi, memperoleh cuti hamil dan melahirkan, serta akses terhadap keluarga berencana. Pelayanan kesehatan ibu adalah tempat yang digunakan untuk menyelenggarakan upaya pelayanan. Pelayanan kesehatan ibu hamil diwujudkan melalui   pemberian pelayanan antenatal sekurang-kurangnya enam kali selama masa kehamilan. Tujuan: Penelitian ini untuk mengetahui Faktor-faktor pengambilan keputusan keluarga dalam pemanfaatan pelayanan kehamilan dan bersalin. Metode Penelitian ini akan menggunakan jenis analitik dengan menggunakan desain cross-sectional. Jumlah sampel dalam penelitian ini adalah 40 orang dengan lama penelitian 7 bulan. Teknik pengambilan total sampling. Analisis data terdiri dari analisis univariat dan analisis bivariat dengan uji chi square. Hasil: Hasil penelitian mayoritas factor pengetahuan baik sebanyak 20 orang, mayoritas factor ekonomi tinggi 21 orang dan faktor jarak tempuh  21 orang.  Kesimpulan: Terdapat hubungan antara factor pengetahuan, ekonomi dan jarak tempuh dengan pemanfaatan pelayanan kehamilan dan bersalin dengan p value 0.000. Penelitian ini diharapkan dapat menjadi masukan bagi pelayanan kehamilan dan persalinan agar dapat lebih maksimal.